The Integration Of Islamic Values In Learning to Conserve Natural Resource: An Effort to Strengthen Students Ecological Awareness - Farhana, Nida; Dewi Prameswari, Meutia; Amirullah, Amirullah (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2022)
This study aims to analyze the integration of Islamic values in fostering ecological awareness in the content of the material presented in the book theme 9